Review of methodology designed to investigate quality of cost data input in life cycle cost - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (Construction Research Institute of Malaysia (CREAM), 2016)
Life Cycle Cost (LCC) estimation process can be divided into three main phases: data inputs, conversion and outputs. The objective of this paper is to identify the most appropriate methodology to investigate the quality of data used as inputs in LCC estimation for building works in the Malaysian construction industry. The focus of quality data here is cost data inputs of building LCC. This paper reports part of a three-year research programme to enhance the quality of LCC outputs through the enhancement of quality data input requirements. A comprehensive literature review was carried out to critically review all the methodologies used to study LCC data inputs in other countries. The goal is to identify the most appropriate methodology to investigate the quality of cost data inputs in LCC analysis of building with regard to the context of Malaysian construction industry. The outcomes of the study proposed that a qualitative research strategy comprises of two approaches, i.e. a literature review and modified Delphi as the most appropriate methodology to critically review and examine behaviours of cost data inputs in LCC analysis of the building based on the opinions from a collective intelligence panellists. The considerable limitation of modified Delphi is to find the appropriate level of panellists that possess skills, knowledge and expertise in the field of LCC. In addition, the Delphi process is normally long and time-consuming because it involves multi-round of questionnaires.